PENERAPAN TEKNIK PERMAINAN GITAR ELEKTRIK GLASSGOW KISS KARYA JOHN PETRUCCI PADA LAGU LEBIH DARI PEMENANG - Candra Gunawan Zebua (Areopagus : Jurnal Pendidikan Dan Teologi Kristen, 2019)
Abstract - The purpose of this study was to describe the playing technique of electric guitar in one of John Petrucci works. The subject of this study is John Petrucci Glassgow Kiss score which has been transcribed into an electric guitar. While the object of his research is John Petrucci Glassgow Kiss guitar playing technique. So that the researcher will apply some of these techniques to a praise song more than the winner. Data analysis techniques are carried out with the stages of analysis before in the field and at the time in the field consisting of data reduction (data reduction), display data (data presentation), and verification (conclusions). The study material in this thesis is done based on the problems the author discussed. Then the results of the data produce conclusions that become problem solving in this thesis. The results of this study that the techniques contained in the work of Glassgow Kiss consist of several parts, namely; Alternate picking, Sweep picking, String skipping, Hammer-On, Pull-Off, Bending, Vibrato, Slide, Arpegio, Palm Mute, and Tapping. From some of these techniques, researchers applied several techniques that were considered capable of adding harmonization that included the structure of the melody into a song of praise more than the winner, including: Palm mute, bending, slide, tapping, hammer on, pull of, skipping strings, alternate picking, and vibrato. Researchers have applied the techniques contained in this work to a "more than a winner" hymn to improve the flow of a more varied melody. So that with the application of techniques that include the structure of melodies in certain times, it will add harmonization to the song More Than Winners.Keywords: Game Technique, Electric Guitar, Glassgow Kiss